Fattening performance and carcass quality of Polish Merino x Romanov crossbred lambs with different proportions of Romanov genotype - Borys B.; Mandecka B. (Production systems and product quality in sheep and goats, 2001)
The aim of this work was to establish the influence of different proportions of the Romanov genotype on the fattening results and slaughter performance of crossbreds with Polish Merino. 36 crossbred ram-lambs with 25-75 per cent Romanov genotype were intensively fattened to the 35-40 kg of body weight, and 16 of them were subjected to post-mortem examination of slaughter performance. No statistically significant influence of the proportion of the Romanov genotype on the fattening results and slaughter performance of lambs was observed, while fattening performance (daily gains, fodder consumption, live evaluation of slaughter performance) and carcass fatness were much lower for crossbreds with a high proportion of the Romanov genotype. The investigation has to be repeated using a greater number of animals.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)